2010
DOI: 10.1016/j.immuni.2010.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Intravital Imaging Reveals Distinct Dynamics for Natural Killer and CD8+ T Cells during Tumor Regression

Abstract: Recognition of NKG2D ligands by natural killer (NK) cells plays an important role during antitumoral responses. To address how NKG2D engagement affects intratumoral NK cell dynamics, we performed intravital microscopy in a Rae-1β-expressing solid tumor. This NKG2D ligand drove NK cell accumulation, activation, and motility within the tumor. NK cells established mainly dynamic contacts with their targets during tumor regression. In sharp contrast, cytotoxic T lymphocytes (CTLs) formed stable contacts in tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
102
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(119 citation statements)
references
References 49 publications
15
102
1
1
Order By: Relevance
“…The slower degranulation kinetics and multiple calcium flux events of mouse CTLs compared with mouse NK cells are consistent with the longer-lived target contact times and sustained calcium signaling profiles observed previously with mouse CTLs (15). Interestingly, NK cells appear to degranulate more quickly upon target cell engagement, irrespective of species.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The slower degranulation kinetics and multiple calcium flux events of mouse CTLs compared with mouse NK cells are consistent with the longer-lived target contact times and sustained calcium signaling profiles observed previously with mouse CTLs (15). Interestingly, NK cells appear to degranulate more quickly upon target cell engagement, irrespective of species.…”
Section: Discussionsupporting
confidence: 86%
“…Importantly, the mode of target cell recognition, engagement, and intracellular signaling events largely underpin their specificity (14). Recent in vivo imaging studies showed that NK cells tend to make transient contacts with their tumor targets, whereas CTLs form longer, more stable contacts (15). The authors suggested these differences in contact time could be explained by differences in calcium responses, with NK cells showing weak calcium influxes, whereas CTLs showed high, sustained calcium influxes.…”
mentioning
confidence: 99%
“…In vitro experiments revealed that, although NKG2D signaling enhanced degranulation, it had little influence on adhesion to target cells, whereas FcR engagment improved adhesion but not degranulation. Using two-photon microscopy, we showed that recognition through FcR affected intratumoral NK cell behavior and promoted long-lasting interactions with targets in vivo, whereas NKG2D signals alone failed to promote NK cell arrest, as we described previously (14). Altogether, our results uncover a novel aspect of cooperation between activating receptors in NK cells and suggest that cell dynamics represent a critical regulator of cell-mediated cytotoxicity.…”
supporting
confidence: 78%
“…Imaging of tumors was performed as described before (14,15) using an upright microscope (DM6000B; Leica) with a water-dipping 253/1.05 NA objective (Olympus). Excitation was provided with a Ti:sapphire laser (Coherent) tuned at 950 nm.…”
Section: Intravital Imaging and Immunofluorescencementioning
confidence: 99%
“…Although it is known that both CTLs and NK cells mediate similar cytotoxic activity (Russell and Ley 2002), this study showed that NK cells had a distinct intratumoral behaviour compared to CTLs. Tumor infiltrating NK cells only formed transient contacts with target cells after initial interaction, whereas CTLs normally establish long lasting contacts that can last for more than 20 minutes (Deguine et al 2011). …”
Section: Visualisation Of Myelomonocytic Cells In Tumors 291mentioning
confidence: 99%